2016
DOI: 10.1111/cogs.12450
|View full text |Cite
|
Sign up to set email alerts
|

First Language Attrition Induces Changes in Online Morphosyntactic Processing and Re‐Analysis: An ERP Study of Number Agreement in Complex Italian Sentences

Abstract: First language (L1) attrition in adulthood offers new insight on neuroplasticity and the role of language experience in shaping neurocognitive responses to language. Attriters are multilinguals for whom advancing L2 proficiency comes at the cost of the L1, as they experience a shift in exposure and dominance (e.g., due to immigration). To date, the neurocognitive mechanisms underlying L1 attrition are largely unexplored. Using event‐related potentials (ERPs), we examined L1‐Italian grammatical processing in 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 140 publications
(230 reference statements)
3
46
0
Order By: Relevance
“…In line with the interpretation that Attriters treated the two critical conditions as outright morphosyntactic violations, we found that Attriters’ acceptability ratings for the two unpreferred relative-clause conditions were not found to differ statistically from ratings the same participants provided in the same experimental session for outright morphosyntactic number agreement violations ( p s > 0.1, see Kasparian et al, 2016). Conversely, the same native-Controls provided significantly higher acceptability ratings for the RC word-orders than for number agreement violations presented in the same experimental session, indicating that they did indeed consider these RC word-orders as more grammatically acceptable than the Attriters.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…In line with the interpretation that Attriters treated the two critical conditions as outright morphosyntactic violations, we found that Attriters’ acceptability ratings for the two unpreferred relative-clause conditions were not found to differ statistically from ratings the same participants provided in the same experimental session for outright morphosyntactic number agreement violations ( p s > 0.1, see Kasparian et al, 2016). Conversely, the same native-Controls provided significantly higher acceptability ratings for the RC word-orders than for number agreement violations presented in the same experimental session, indicating that they did indeed consider these RC word-orders as more grammatically acceptable than the Attriters.…”
Section: Resultssupporting
confidence: 83%
“…The opposite was found in a recent ERP study of number agreement processing in Italian by Kasparian et al (2016). Although attriters (L1-Italian, L2-English) scored numerically lower on a number of written and oral proficiency measures, the only behavioral difference from native-controls that reached significance was the attriters’ longer response times during the online acceptability judgment task.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…We limit the features we discuss to relatively global measures that can be compared between a bilinguals’ two languages and exclude more language-specific features, such as tense and aspect (e.g., Montrul, 2008) or number agreement (Kasparian et al, 2017). …”
mentioning
confidence: 99%